Development of Android-Based Starter Motor Learning Media for Improving Students 'Abilities and Knowing its Learning Motivated Achievements - Ibnu Mubarak; Tatang Permana; Iyep Sutia; Rika Andriani; S Sriyono; Ridwan Adam MN (VANOS Journal of Mechanical Engineering Education, 2021)
This study aims to develop Android-based learning media to improve students' abilities regarding the reduction type starter motor system and to determine the acquisition of learning motivation. The method used is pre-experimental design in the form of one-group pretest-posttest, while media development uses the ADDIE method. The population of this study were students who contracted electricity courses. The results of this study indicate an increase in the learning outcomes of the Pre-Test and Post-Test which is significant with the acquisition of the significance test using the t test with a significance value of 0.000, this increase is due to the use of android-based learning media that has been made. So that this learning media has a good impact on increasing students' insight in using technology, especially Android for learning uses. In addition, the students' learning motivation on average is in the category motivated by this media.